2018
DOI: 10.3390/foods7070104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Kinds and Ratios of Vegetable Oils on Ice Cream Quality Characteristics

Abstract: The aim of this study was to develop ice cream products using different types of oils, a sensory ballot to focus on the textural attributes of new ice cream products, evaluate physicochemical properties of these products and physical measurements. Milkfat, hazelnut oil and olive oil were mixed at different concentrations for a total of 12% fat. Control sample contains 12% milk fat while the other formulations contain different proportion of milk fat, hazelnut oil and olive oil as the fat content. The combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…In addition, both 75% and 100% ice milk treatments were full melted after 50 min, while, other treatments showed more resistance, actually 88, 90, and 100 % for control, 25 and 50% treatments respectively. These results are nearly in agreement with those reported by Nazaruddin et al, (2008) and Guven et al, (2018). This increase in melting rate were related to the increase of substitution of milk fat with RPO, which may be attributed to the lower melting point of the RPO.…”
Section: Overrun and Melting Rate Of Ice Milk And Their Different Tresupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, both 75% and 100% ice milk treatments were full melted after 50 min, while, other treatments showed more resistance, actually 88, 90, and 100 % for control, 25 and 50% treatments respectively. These results are nearly in agreement with those reported by Nazaruddin et al, (2008) and Guven et al, (2018). This increase in melting rate were related to the increase of substitution of milk fat with RPO, which may be attributed to the lower melting point of the RPO.…”
Section: Overrun and Melting Rate Of Ice Milk And Their Different Tresupporting
confidence: 93%
“…The reduced aeration is reasonable for this decrease in overrun, as the oilier nature of RPO may not be enough to withstand the physical structure that support the air cells introduced during whipping. Moreover, the nature of high viscosity for fruits pulp, which had a negative effect on the overrun values, these results are nearly in agreement with those reported by Bajwa et al, (2003) and Guven et al, (2018).…”
Section: Overrun and Melting Rate Of Ice Milk And Their Different Tresupporting
confidence: 92%
“…In general, the brightness ( L *) of the ice cream increased significantly with increased fat content [ 30 ]. However, the a * values showed the opposite results, as also reported by Güven et al [ 15 ]. The yellowness ( b *) of T1 and T3 was significantly ( p < 0.05) lower than that of other ice cream treatments, although the fat contents of T2, T4, and T5 were similar, and the b * value directly corresponded to the fat content of ice cream [ 6 ].…”
Section: Resultssupporting
confidence: 62%
“…For example, adding milk fat to ice cream lowers the ice phase volume and stabilizes air bubbles, which are sensory qualities that are expected in ice cream [ 12 , 13 , 14 ]. In addition, these qualities affect the texture and color development of ice cream [ 15 ]. Higher consumption of fat increases the risk of obesity, diabetes, and coronary heart disease [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a blend of palm oil and butter at appropriate ratios showed a higher oxidation stability in comparison to either components (Abd El‐Aziz et al, 2013). In another study (Güven et al, 2018), sunflower oil was combined with milk fat to enhance the mouthfeel for ice cream products. Moreover, a recent study reported that the presence of milk fat could contribute to enhance the “cooling sensation” during consumption of fat spread products (Galindo‐Cuspinera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%